2015
DOI: 10.1111/his.12851
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of inflammatory pseudotumour‐like follicular dendritic cell tumour of the abdomen

Abstract: Inflammatory pseudotumour-like FDC tumour should be differentiated from inflammatory myofibroblastic tumour, Hodgkin lymphoma, interdigitating dendritic cell sarcoma, and gastrointestinal stromal tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 16 publications
1
76
0
Order By: Relevance
“…Extensive epithelioid granulomas and eosinophilic abscess formation can be rarely seen within the tumor . Studies have demonstrated positive EBER by in situ hybridization in almost all cases, frequent expression of the oncogenic protein EBV‐latent membrane protein‐1 by immunohistochemical stain, and monoclonal episomal EBV by southern blot analysis, suggesting a pathogenic role of EBV in this tumor …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive epithelioid granulomas and eosinophilic abscess formation can be rarely seen within the tumor . Studies have demonstrated positive EBER by in situ hybridization in almost all cases, frequent expression of the oncogenic protein EBV‐latent membrane protein‐1 by immunohistochemical stain, and monoclonal episomal EBV by southern blot analysis, suggesting a pathogenic role of EBV in this tumor …”
Section: Discussionmentioning
confidence: 99%
“…The tumor cells have morphologic, ultrastructural, and immunophenotypic features resembling those of normal follicular dendritic cells and can occur in both nodal and extranodal sites. Inflammatory pseudotumor‐like FDC sarcoma is regarded as a separate entity due to selective involvement to the liver and spleen, distinct pathologic features, and strong association with EBV . The tumor typically presents as a large, solitary, well‐circumscribed mass in liver or spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1996 to date we retrieved 22 publications reporting IPT-like FDC tumors [11,15,35,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. There were 46 patients described: 24 female, 22 male (ratio 1.1:1), median age 57y (range 29-79y).…”
Section: Follicular Dendritic Cell Tumors Of the Spleenmentioning
confidence: 99%
“…IPT-like FDC tumors of liver are even more rare, and the clinicopathological nature of this type of disease remains unknown. First, the most common presentation of patients with FDC tumors is abdominal pain or weight loss, but IPT-like FDC tumors often grow without clinical symptoms or abdominal discomfort, as was the case in our patient (9). Second, IPT-like FDC tumors always exhibit a marked female predominance (10).…”
Section: Discussionmentioning
confidence: 65%